Grapevine pruning systems and cultivars influence the diversity of wood-colonizing fungi. (December 2016) - Travadon, Renaud; Lecomte, Pascal; Diarra, Barka; Lawrence, Daniel P.; Renault, David; Ojeda, Hernán; Rey, Patrice; Baumgartner, Kendra
Abstract: Grapevine wood hosts diverse fungal species, including pathogens that cause grapevine trunk diseases and wood decomposers, with detrimental effects on yields. This study focuses on the effects of two pruning systems, minimal (min-) or spur-pruning, on the community of trunk pathogens and other wood-colonizing fungi in the trunks of two cultivars, Mourvèdre and Syrah. Culture and DNA-based methods were used to describe the fungal communities. In both cultivars, especially Syrah, spur-pruned vines had more wood necrosis than min-pruned vines, and the community of spur-pruned Syrah was distinguished by its single-stranded conformational polymorphism (SSCP) profile. Diversity profiles of all 88 cultivated taxa and canonical correspondence analyses of the 15 most frequently isolated taxa revealed differences in community structure due to pruning system, trunk location, and/or wood type. Greater levels of wood necrosis may be due to the composition of the fungal community rather than to a greater diversity of taxa.